PENGARUH PRODUCT ATTRIBUTE, BRAND TRUST, DAN CUSTOMER SATISFACTION TERHADAP PURCHASE INTENTION PADA PRODUK RICE BOWL - abellia, syafira; Immanuel, Dewi (Universitas Ciputra Surabaya, 2024)
This study aims to determine the effect between product attributes, brand trust, and customer satisfaction on purchase intention of rice bowls. This analysis using SPSS 25 Multiple Linear Analysis was used in this study, the population in this study were consumers who had consumed rice bowls. The sample was taken using purposive sampling method with a total of 385 respondents. Data collection in this study was carried out by distributing questionnaires online to rice bowl consumers in Jakarta and Surabaya. Respondents in this study were consumers aged 17-27 years totaling 295 respondents, respondents with an age range of 27-37 years totaled 62 respondents, while respondents over 47 years of age were 28 respondents. there were a total of 385 respondents with 173 respondents residing in Jakarta and 212 respondents residing in Surabaya. The results of this study found that product attribute, brand trust, and customer satisfaction have a positive and significant effect on purchase intention. Based on the t-statistic value test that has been carried out, it is known that the product attribute has a t-statistic value of 0.000 <0.005 has a significant positive effect on purchase intention, the brand has a t-statistic significance value (Sig.) 0.000 <0.005, it can be interpreted that there is a significant influence between Brand Trust on Purchase intention, and the significance value of customer satisfaction.